Publish or Perish: What the Competition is Really Doing - ZIVNEY, TERRY L.; BERTIN, WILLIAM J. (Journal of Finance, 1992)
ABSTRACT This study provides comprehensive publications performance data over a 25‐year period for finance doctorates. These data indicate that publishing one article per year in any finance journal (or finance, accounting, economics, or business journal) over any prolonged period of time is a truly remarkable feat, met by only 5% of the graduates. Tenure screens combining various quantity and quality requirements are examined to assess their ability to predict future publication productivity. Faculty and administrators seeking defensible benchmarks for evaluating faculty research productivity in finance will find that these data and results are particularly useful.